The antiproliferative study of quercus infectoria galls crude and micelle extract hydrogel beads against selected breast cancer cells - Wan Nur Suzilla, Wan Yusuf (2024)
Hydrogel beads are used in scientific studies to investigate the potential of natural extracts in inhibiting cancer cell growth. They provide stability and transportation by enclosing the extract within a network, ensuring its antiproliferative properties. They can also be engineered for controlled release, ensuring consistent antiproliferative effects. Additionally, they prevent agglutination, ensuring uniform distribution of the extract, and potentially enhancing its efficacy. Hence, in this study, Quercus infectoria (QI) galls hydrogel beads incorporated with QI galls crude and micelle extracts were developed to overcome the micelle aggregation and stability problem as well as a new alternative in cancer treatment. QI galls crude extract was produced using maceration extraction with 70% aqueous ethanol while QI galls crude extract loaded micelle was formulated using solvent casting method and then both extracts were characterized for their physicochemical properties. Then, the QI galls crude and micelle extract were incorporated into hydrogel beads via crosslinking action between polymer (pectin) and crosslinker (zinc acetate). All crude extract, micelles and hydrogel beads were tested against selected breast cancer cells (MCF-7 and MDA-MB-231) to determine the antiproliferative activity using MTT Assay as well as for apoptosis activity via FITCAnnexin V staining. From the findings, it was observed that the QI galls crude extract, micelles and hydrogel beads exhibited good antiproliferative activity against breast cancer cells (MCF-7 and MDA-MB-231) but showed no cytotoxicity against normal cell line, L929 apart from induced the cell death mechanism through apoptosis. All formulated micelles showed a good size range (below 20 nm), with polydispersity index (PDI) value between 0.1-0.4 indicating narrow distribution and negatively charged. Based on the surface chemistry analysis, it was observed that all formulated micelles, had almost similar relative ratio amongst the suggested chemical bonds and in accordance with those reported in pure vitamin E TPGS. For extract loading, it was showed that Quercus infectoria Vitamin E TPGS (QIT) micelle gave highest loading (110.41 µg/ml) as compared to other micelles and the surface morphology by Transmission Electron Microscope (TEM), showed all formulated micelles were in moderate uniformity with nearly spherical shape. Controlled drug release profile showed all micelles demonstrated biphasic release pattern while the cellular uptake was increased with prolonged incubation time. QIT micelle showed highest cytotoxic activity (IC50 8.28±0.82 µg/ml) against MCF-7 cells with faster onset of action as compared to MDA-MB-231 (IC50 11.09±0.73 µg/ml) and induced apoptotic cell death mechanism with no toxicity effect against normal cells, L929. For the hydrogel beads formulation, two different hydrogel beads were formulated, using QI crude (QIC) and micelle (QIM) extract. From the findings, it was showed both formulated beads, demonstrated good yield, morphology, swelling ability, swelling time and moisture content (below 20%). As conclusion, a novel polymeric hydrogel beads incorporated with QI galls crude and micelle extract with good antiproliferative activity against selected breast cancer cells were successfully formulated and presents a promising strategy for safeguarding the integrity of extracts by improving their stability and effectively preventing undesirable aggregation.